Si verum dicimus, haec est mea germana patria (Cic. leg. 2, 3) - Gamberale, Leopoldo (Ciceroniana On Line, 2020)
This paper offers a rereading of the “setting” of De legibus, in the countryside near the house where Cicero was born. In particular, it focuses on the beginning of Book II (§§ 1-7), with the goal of re-examining the praise of his birthplace and the problem of having “two homelands”, unam naturae, alteram civitatis, or, as well, alteram loci patriam, alteram iuris (leg. 2, 5). Cicero’s reflections in De legibus 2, 1-7 turn out to be potentially relevant for our contemporary world and its globalization, in which we must confront large-scale immigration issues, reconsider difficulties of citizenship, and deal with ideas of national sovereignty and regional feelings in an ongoing fashion.